Easy-Mushroom Mobile Application Using the Internet of Things (IoT) - K. Thapwiroch; A. Kumlue; N. Saoyong; P. Taprasan; S. Puengsungewan (Universitas Pendidikan Indonesia (UPI), 2021)
The cultivation of mushrooms is not a simple task for traditional mushroom farmers, because the productivity of the mushroom farm depends on the ability to regulate the environment surrounding the mushroom farm. In addition, another problem for traditional mushroom farmers is that they cannot grow various types of mushrooms related to marketing. This research presents a mobile application for assisting mushroom farmers to understand the growing situation. The proposed mobile application called the easy mushroom application is based on the Internet of things (IoT) concept. The easy mushroom has been designed to analyse the humidity and light intensity relationship at a specific time. The experimental results show that the Easy-Mushroom mobile application provides a relationship between light intensity, humidity, and tolerance humidity level of mushroom.